Correlation of growth temperature with stress, defect states and electronic structure in an epitaxial GaN film grown on c-sapphire via plasma MBE. Issue 11 (26th February 2016) - Krishna, Shibin; Aggarwal, Neha; Mishra, Monu; Maurya, K. K.; Singh, Sandeep; Dilawar, Nita; Nagarajan, Subramaniyam; Gupta, Govind
Abstract : Stress engineering is shown to have a significant influence on the defect states, surface morphology and electronic properties of a GaN film grown on c -sapphire. Abstract : The relationship of the growth temperature with stress, defect states, and electronic structure of molecular beam epitaxy grown GaN films on c -plane (0001) sapphire substrates is demonstrated. A minimum compressively stressed GaN film is grown by tuning the growth temperature. The correlation of dislocations/defects with the stress relaxation is scrutinized by high-resolution X-ray diffraction and photoluminescence measurements which show a high crystalline quality with significant reduction in the threading dislocation density and defect related bands. A substantial reduction in yellow band related defect states is correlated with the stress relaxation in the grown film. Temperature dependent Raman analysis shows the thermal stability of the stress relaxed GaN film which further reveals a downshift in the E2 (high) phonon frequency owing to the thermal expansion of the lattice at elevated temperatures. Electronic structure analysis reveals that the Fermi level of the films is pinned at the respective defect states; however, for the stress relaxed film it is located at the charge neutrality level possessing the lowest electron affinity. The analysis demonstrates that the generated stress not only affects the defect states, but also the crystal quality, surface morphology and electronic structure/properties.